EFFICACY OF MURRAYA KOENIGII LEAF EXTRACT FOR ATTENUATING THE PROGRESSION OF DIABETIC NEPHROPATHY IN ANIMAL MODELS - LADLI KUMARI; PAPIYA MITRA MAZUMDER (International Journal of Pharma and Bio Sciences, 2013)
Diabetes was induced in male adult albino rats by injecting streptozotocin (65 mg/kg b.wt., i.p.) and left untreated for 9 weeks for the development of nephropathy. Animals were treated with methanolic extract of Murraya koenigii (L.) Spreng leaf (MEMK) at two dose levels (200 mg/kg and 400mg/kg) and with standard drug Glimipride (2mg/kg) for 40 days in order to analyse its renoprotective effect, by evaluating metabolic profile, renal function test, electrolyte concentration in blood and urine along with its antioxidant status and histopathological studies. Nephropathy was noted in diabetic rats between 8th-9th week by assessing significant increase in polyuria, proteinuria, serum glucose, albuminuria, creatinine and blood urea nitrogen levels. On 40 days of treatment of MEMK, serum glucose, total cholesterol, HDL- cholesterol, triglyceride including the kidney functions were greatly improved as evidenced by amelioration of blood urea nitrogen, creatinine, serum inulin, total protein concentration, albumin and serum electrolytes (Type IV renal tubular acidosis) and also improvement in antioxidant with decrease in malodialdehyde and increase in catalase, superoxide dismutase and glutathione-s-transferase levels. Histopathological studies of nephropathic animals showed chronic glomerulonephritis with marked improvementin treatment groups. Data from this study suggest that M. koenigii (L.) Spreng leaf possesses a protective effect and attenuates the progression of diabetic nephropathy in animals.